2016
DOI: 10.15517/ap.v30i121.23458
|View full text |Cite
|
Sign up to set email alerts
|

Health Action Process Approach (HAPA) as a Theoretical Framework to Understand Behavior Change

Abstract: Abstract.A theoretical framework to explain, predict, and modify health behaviors is presented which consists of various psychological constructs and a mediator mechanism. Risk perception, outcome expectancies, self-efficacy, intention, planning, and action control constitute the building blocks for a mediator model that is based on two processes: goal setting and goal pursuit. When it comes to the development of interventions to modify behaviors, one can target either the initial motivation phase or the subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
168
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(180 citation statements)
references
References 22 publications
8
168
2
2
Order By: Relevance
“…The results of this study support a phase-specific approach to behaviour change (Schwarzer, 2008(Schwarzer, , 2016 and highlight the importance of sequentially targeting different beliefs and skills to facilitate successful initiation and maintenance of behaviour. At the beginning of the exercise programme, task self-efficacy was the strongest predictor of attendance, although by 12 months, the relationship was small and negative, suggesting that behaviour is no longer dependent on whether one feels capable of performing it.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…The results of this study support a phase-specific approach to behaviour change (Schwarzer, 2008(Schwarzer, , 2016 and highlight the importance of sequentially targeting different beliefs and skills to facilitate successful initiation and maintenance of behaviour. At the beginning of the exercise programme, task self-efficacy was the strongest predictor of attendance, although by 12 months, the relationship was small and negative, suggesting that behaviour is no longer dependent on whether one feels capable of performing it.…”
Section: Discussionsupporting
confidence: 63%
“…While some reviews have concluded theory-based interventions are more effective than non-theory-based interventions (e.g., Taylor, Conner, & Lawton, 2012;Webb, Joseph, Yardley, & Michie, 2010), others have not (e.g., Prestwich et al, 2014;Roe, Hunt, Bradshaw, & Rayner, 1997). An emergent approach to understanding health behaviour change distinguishes between behavioural initiation and maintenance phases as well as the beliefs (e.g., self-efficacy, outcome satisfaction), skills, and strategies that support self-regulatory efforts during each phase (Rothman, 2000;Schwarzer, 2008Schwarzer, , 2016. An emergent approach to understanding health behaviour change distinguishes between behavioural initiation and maintenance phases as well as the beliefs (e.g., self-efficacy, outcome satisfaction), skills, and strategies that support self-regulatory efforts during each phase (Rothman, 2000;Schwarzer, 2008Schwarzer, , 2016.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The psychological changes resulting from the HAPA approach predicted behaviour changes resulting in 12-month biophysical changes and support the theoretical basis of the intervention (Fig. 2) [1213141516]. …”
Section: Evidence From Evaluative Trialssupporting
confidence: 60%
“…Last, social support can increase the likelihood of successful action control by promoting coping planning and recovery self-efficacy (Schwarzer, 2016). Coping plans address how to respond to unexpected obstacles, barriers, and risky situations that arise during continued goal pursuit and endanger both immediate and longer-term self-regulatory success (Sniehotta, Scholz, & Schwarzer, 2005).…”
Section: Coping Planning and Recovery Self-efficacymentioning
confidence: 99%